Numerical approach to frictional fingers - Bjornar Sandnes (Physical Review E, 2015)
Experiments on confined multiphase flow systems, involving air and a dense suspension, have revealed a diverse set of flow morphologies. As the air displaces the suspension, the beads that make up the suspension can accumulate along the interface. The dynamics can generate “frictional fingers” of air coated by densely packed grains. We present here a simplified model for the dynamics together with a new numerical strategy for simulating the frictional finger behavior. We further make theoretical predictions for the characteristic width associated with the frictional fingers, based on the yield stress criterion, and compare these to experimental results. The agreement between theory and experiments validates our model and allows us to estimate the unknown parameter in the yield stress criterion, which we use in the simulations.